Indigenizing Climate Policy in Canada: A Critical Examination of the Pan-Canadian Framework and the ZéN RoadMap - Reed, Graeme; Gobby, Jen; Sinclair, Rebecca; Ivey, Rachel; Matthews, H. Damon (Frontiers in Sustainable Cities, 2021)
Climate policies and plans can lead to disproportionate impacts and benefits across different kinds of communities, serving to reinforce, and even exacerbate existing structural inequities and injustices. This is the case in Canada where, we argue, climate policy and planning is reproducing settler-colonial relations, violating Indigenous rights, and systematically excluding Indigenous Peoples from policy making. We conducted a critical policy analysis on two climate plans in Canada: the Pan Canadian Framework on Clean Growth and Climate Change (Pan-Canadian Framework), a federal government-led, top-down plan for reducing emissions; and the Québec ZéN (zero émissions nette, or net-zero emissions) Roadmap, a province-wide, bottom-up energy transition plan developed by civil society and environmental groups in Quebec. Our analysis found that, despite aspirational references to Indigenous Peoples and their inclusion, both the Pan-Canadian Framework and the ZéN Roadmap failed to uphold the right to self-determination and to free, prior, and informed consent, conflicting with commitments to reconciliation and a “Nation-to-Nation” relationship. Recognizing these limitations, we identify six components for an Indigenous-led climate policy agenda. These not including clear calls to action that climate policy must: prioritize the land and emphasize the need to rebalance our relationships with Mother Earth; position Indigenous Nations as Nations with the inherent right to self-determination; prioritize Indigenous knowledge systems; and advance climate-solutions that are interconnected, interdependent, and multi-dimensional. While this supports the emerging literature on Indigenous-led climate solutions, we stress that these calls offer a starting point, but additional work led by Indigenous Peoples and Nations is required to breathe life into a true Indigenous-led climate policy.